B‐cell very late antigen‐4 deficiency reduces leukocyte recruitment and susceptibility to central nervous system autoimmunity. Issue 5 (28th March 2015) - Lehmann‐Horn, Klaus; Sagan, Sharon A.; Bernard, Claude C.A.; Sobel, Raymond A.; Zamvil, Scott S.
<x xml:space="preserve">Abstract</x> Natalizumab, which binds very late antigen‐4 (VLA‐4), is a potent therapy for multiple sclerosis (MS). Studies have focused primarily upon its capacity to interfere with T‐cell migration into the central nervous system (CNS). B cells are important in MS pathogenesis and express high levels of VLA‐4. Here, we report that the selective inhibition of VLA‐4 expression on B cells impedes CNS accumulation of B cells, and recruitment of Th17 cells and macrophages, and reduces susceptibility to experimental autoimmune encephalomyelitis. These results underscore the importance of B‐cell VLA‐4 expression in the pathogenesis of CNS autoimmunity and provide insight regarding mechanisms that may contribute to the benefit of natalizumab in MS, as well as candidate therapeutics that selectively target B cells. Ann Neurol 2015;77:902–908